2017
DOI: 10.1098/rsta.2017.0064
|View full text |Cite
|
Sign up to set email alerts
|

Efficient utilization of renewable feedstocks: the role of catalysis and process design

Abstract: Renewable carbon feedstocks such as biomass and CO present an important element of future circular economy. Especially biomass as highly functionalized feedstock provides manifold opportunities for the transformation into attractive platform chemicals. However, this change of the resources requires a paradigm shift in refinery design. Fossil feedstocks are processed in gas phase at elevated temperature. In contrast, biorefineries are based on processes in polar solvents at moderate conditions to selectively de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…For this reintroduction and revamping of the productive cycle, the appropriate processes and rather smart technologies need to be developed and applied within a much improved and integrated manufacturing system empowered by the latest and states of the art techniques such as enterprise resource planning (ERP), balancing, modernization, and replacement (BMR), etc. Most of these technologies can be used to ensure manufacturing through the usage of green and clean methods of energy conversion, renewable resources, and achieving greater efficiency in catalytic syntheses (Belhadi et al 2021 ; Catlow et al 2020 ; Palkovits and Delidovich 2017 ; Sheldon 2016 ; Zhang et al 2018 ; Wang et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reintroduction and revamping of the productive cycle, the appropriate processes and rather smart technologies need to be developed and applied within a much improved and integrated manufacturing system empowered by the latest and states of the art techniques such as enterprise resource planning (ERP), balancing, modernization, and replacement (BMR), etc. Most of these technologies can be used to ensure manufacturing through the usage of green and clean methods of energy conversion, renewable resources, and achieving greater efficiency in catalytic syntheses (Belhadi et al 2021 ; Catlow et al 2020 ; Palkovits and Delidovich 2017 ; Sheldon 2016 ; Zhang et al 2018 ; Wang et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This results in a significantly higher oxygen content of biomass and several biomass‐based products as compared to fossil feedstock‐derived hydrocarbons. This functional diversity leads to challenges in catalysis, process design and separation but also offers several opportunities to access novel products of tailored functionality , . The major constituents of lignocellulose are cellulose, a linear polymer of glucose, hemicelluloses, a branched polymer composed of various C 5 ‐ and C 6 ‐carbohydrates and lignin, a polymer of randomly polymerized p ‐coumaryl‐, coniferyl and synapyl alcohols (Fig.…”
Section: Biomass As Renewable Resourcementioning
confidence: 99%
“…[35][36][37] In addition to the aforementioned technical advantages, HMES also opens new reaction pathways distinct from thermochemical and thermocatalytic routes and that can give access to new products that are hardly obtainable through conventional transformations. 16,18,19,38,39 Recently, our group explored the electrohydrogenation of cis,trans-muconic acid (ctMA) and demonstrated that the reaction can take place directly upon fermentation with metabolically-engineered S. cerevisiae using protons provided by the acidic ( pH 4) broth. 16,18,19 This electrohydrogenation produced the novel compound trans-3-hexenedioic acid (t3HDA) with near stoichiometric yields and close to 100% faradaic efficiency (FE) using a lead cathode.…”
Section: Introductionmentioning
confidence: 99%